Mechanical properties of hybrid PVA fibre reinforced cementitious composites under bending - Ahmed, Shaikh; Mihashi, H.; Suzuki, S. (Canadian society for civil engineers, 2006)
Experimental results on the strain hardening and multiple cracking behaviour of polyvinyl alcohol (PVA) fibre reinforced cementitious composites under bending are reported in this paper. Different hybrid combinations of PVA fibres with different lengths and volume fractions are considered to reinforce the mortar matrix. Among different hybrid combinations, the composite containing 2% RECS100 PVA fibres of 12mm length and 1% REC15 PVA fibres of 6 mm length and the composite containing 2% RECS100 PVA fibres of 24mm length and 1% REC15 PVA fibres of 8 mm length showed the best performance in terms of highest ultimate load, largest CMOD and multiple cracking behaviour. The effects of light weight sand on the strain hardening and multiple cracking behaviour of hybrid fibre composites are also evaluated in this study. It has been observed that the ultimate load and CMOD at peak load for all light weight hybrid fibre composites are almost the same irrespective of volume fractions of light weight sand. The composites containing "u" and "FL0" type light weight sand exhibited higher ultimate load than those containing "FL1" and "FL2" type light weight sand. It was also observed that the hybrid fibre composite containing normal sand exhibited a higher ultimate load than the composites with light weight sands.